Odpowiedzi

2010-01-19T09:03:19+01:00
- x+y/2 + 5x-y/3=7x-3y/5 /*30
3/y+1=5/x-1 /*(y+1(x-1)

-15x-15y+50x-10y=42x-18y
3(x-1)=5(y+1)

35x-42x=-18y+25y
3x-3=5y+5

-7x=7y /:7
3x-8=5y

y=-x
3x-8=-5x
→3x+5x=8
→8x=8 /:8
→x=8
y=-8
x=8

b) y-4=12x
-1-2(x-2y)=-(x-2)²-(3-x)(x+3)

y=12x+4
-1-2x+4y=-x²+4x-4-3x-9+x²+3x

y=12x+4
-2x+4(12x+4)-4x+3x-3x=-13+1
→-6x+48x+16=-12
→54x=-12-16
→54x=-28 /:54
→x=-14/27
y=12*(-14/27)+4
→y=-6i2/9+4
→y=-2i2/9
x=-14/27
y=-2i2/9

c) 2y-(x-3)²=-48-(x-5)(5+x)
y+x/2-x-y/4=o,75 /*4

2y-(x²-6x-9)=-48-(5x+x²-25-5x)
2y+2x-x+y=3

2y-x²+6x+9=-48+25
3y-x=3

2y+6x=-23-9
-x=3-3y /*(-1)

2y+6x=-32
x=3y-3
→ 2y+6(3y-3)=-32
→ 2y+18y-18=-32
→ 20y=-32+18
→ 20y=-14 /:20
→ y=-0,7
x=3(-0,7)-3
→ x=-2,1-3
→x=-5,1
x=-5,1
y=-0,7

d)
3[2(x-1/6y)-1]=-2y+6x
2[3(x-y)-9/4]=-6y+3x

3(2x-1/3y-1)=-2y+6x
2(3x-3y-9/4)=-6y+3x

6x-y-3=-2y+6x
6x-6y-4,5=16y+3x

y=3
3x=4,5 /:3

y=3
x=1,5